A mechanically robust self-healing binder for silicon anode in lithium ion batteries. (March 2021) - Chen, Hao; Wu, Zhenzhen; Su, Zhong; Chen, Su; Yan, Cheng; Al-Mamun, Mohammad; Tang, Yongbing; Zhang, Shanqing
Abstract: Both industrious and academic research societies have considered silicon (Si) as the most promising anode for next-generation lithium ion batteries (LIBs) because silicon offers more than one order of magnitude higher capacity than conventional anode materials. However, huge volume changes and pulverization of the silicon particles during the charge/discharge processes damage the longevity of Si-based LIBs. Self-healing binders could tackle this problem by in-situ repairing the damage to the silicon anode. Herein, we synthesized a novel self-healing poly(ether-thioureas) (SHPET) polymer with balanced rigidity and softness for the silicon anode. The as-prepared silicon anode with the self-healing binder exhibits excellent structural stability and superior electrochemical performance, delivering a high discharge capacity of 3744 mAh g −1 at a current density of 420 mA g −1, and achieving a stable cycle life with a high capacity retention of 85.6% after 250 cycles at a high current rate of 4200 mA g −1 . The success of this work suggests that the proposed SHPET binder facilitates fast self-healing, buffers the drastic volume changes and overcomes the mechanical strain in the course of the charge/discharge process, and could subsequently accelerate the commercialization of the silicon anode. Graphical Abstract: A self-healing poly(ether-thioureas) (SHPET) polymer is synthesized via a one-step polycondensation reaction. The SHPET binder could effectively buffer the volume changes of Si@SHPET anode and maintain the electrode integrity during the prolonged cycles due to the fast self-healing ability and patching function from dislocation and reformation of H-bonds. ga1 Highlights: A mechanically robust self-healing polymer (SHPET) is synthesized via a facile polycondensation reaction. Balanced softness and hardness of the SHPET polymer facilitate rapid self-healing. The as-prepared Si-SHPET anode delivers excellent rate capability and improved cycling stability. The cracks and damages in the as-prepared Si anode can be recovered by the SHPET binder.